THE INFLUENCE OF PERCEIVED EASE OF USE, TRUST, PERCEIVED RISK, AND PRICE DISCOUNTS ON CONSUMER PURCHASE INTENTION FOR FASHION PRODUCTS ON SHOPEE E-COMMERCE PLATFORM: A CASE STUDY IN HULU SUNGAI UTARA - Syahrusiani, Syahrusiani; Amastya, Gangga Fiiki (Inovatif Jurnal Administrasi Niaga, 2025)
This study aims to test the significance of ease of use, trust, risk perception and price discounts on consumer purchasing interest in fashion products. This study uses a quantitative method with purposive sampling technique with questionnaires distributed to 75 respondents. The results of the research regression test show that the variables of ease of use and risk perception do not have a statistically significant effect on purchasing interest, in the context of this study both are not strong enough to directly encourage purchasing interest. The trust variable shows a potential influence with a t-value (1,734) that exceeds the t-table (1,666) although the significance is still above 0.05. Meanwhile, price promotions/discounts are proven to have a significant effect on purchasing interest with a t-value (2,563) that exceeds the t-table (1,666) and a significance of 0,013 <0,05. Based on the results of the study, it is recommended for business actors to focus more on optimizing price discount strategies to increase consumer purchasing interest.